2015
DOI: 10.1111/obr.12320
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of obesity and infections

Abstract: There is evidence that certain infections may induce obesity. Obese persons may also have more severe infections and have compromised response to therapies. The objective of this study is to review the available literature identifying infections that potentially contribute to greater body mass index (BMI) and differential responses of overweight and obese persons to infections. A systematic literature review of human studies examining associations between infections and weight gain, differential susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 214 publications
2
109
0
7
Order By: Relevance
“…Given that patients with higher BMI have a reduced response to prophylaxis, adjustments of drug doses may also be considered. 48 Our study has several limitations. First, the major limitation of the study is the lack of actual health care cost data.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that patients with higher BMI have a reduced response to prophylaxis, adjustments of drug doses may also be considered. 48 Our study has several limitations. First, the major limitation of the study is the lack of actual health care cost data.…”
Section: Discussionmentioning
confidence: 91%
“…Concerted efforts to reduce the incidence of infection and perioperative blood glucose are likely to be effective in reducing prolonged LOS and associated costs. Given that patients with higher BMI have a reduced response to prophylaxis, adjustments of drug doses may also be considered …”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of obesity more than doubled between 1980 and 2014. Obesity is associated with infectious diseases, such that certain infections may trigger an increase in adiposity, such as human adenovirus 36, H1N1/influenza virus, human immunodeficiency virus, and Helicobacter pylori ( H. pylori )[1]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported a higher H. pylori prevalence in obese patients[7,8]. The systematic review by Dhurandhar et al[1] reported an increase in weight gain or an increase in the biomarkers associated with weight gain after H. pylori eradication, and most cross-sectional studies found evidence of a higher prevalence of H. pylori infection in obese individuals or metabolic impairment in the presence of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, obesity has been associated with an increased risk of both bacterial and viral infections, at several body sites, and nosocomial and surgical site infections . Obese patients are also more likely to get more severe infections than their nonobese counterparts, and carry poorer prognosis with higher risk of resistance to treatment . This increased infection risk is probably attributable to metabolically active visceral fat, as opposed to subcutaneous fat.…”
mentioning
confidence: 99%